Pengaruh Metode Latihan Interval Terhadap Kapasitas Vo2 Maksimal Fisik Atlet Sepak Bola Klub Junior BBT FC - Candra, Rafi; Asnawati, Asnawati; Personi, Megi (CV. Generasi Insan Rafflesia, 2024)
This research includes experimental research, where the research is intended to see the effect of one independent variable on one dependent variable. The independent variable is Interval training (X) while the dependent variable is the increase in maximum oxygen volume (VO2Max) (Y). The sampling technique in this study was total sampling. The instrument used in this study was the VO2Max test by using the Multistage Fitness Test (Bleep test). Based on the results of data analysis, the obtained Thitung value of 16.67227 is greater than the Ttable value of 1.72913, thus it can be concluded that this study has the effect of Interval Training on increasing the VO2Max of BBT FC football athletes in Tapus Village, South Lebong District, Lebong Regency. Furthermore, the percentage increase in the effect of interval training on increasing VO2Max in BBT FC football athletes in Tapus Village, South Lebong District, Lebong Regency is 7.62%. The conclusion of this study is that there is a significant effect of interval training on vo2max of BBT FC football athletes in Tapus Village, South Lebong District, Lebong Regency.